2018
DOI: 10.14299/ijser.2018.04.03
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Power Compensation Improvement Technique for Injection Substations in Nigeria

Abstract: Abstract:The contemporary power system is intricate in structure, it comprises of enormous number of distinct static and dynamic devices. The ever increasing demand for electrical power by consumers on the existing AC transmission power system via injection station due to urbanization poses challenges of voltage thicker, voltage instability, overloaded lines and congestion of lines thus exceeding their thermal limits which result to malfunction and eventually breakdown of transformers due to stress. In this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Advanced techniques like ANNs and ensemble methods, as well as statistical methods like ARIMA and Bayesian time series analysis, are effective in achieving high-accuracy predictions. In the work of [10], exponential regression was used to analyze and forecast the load needed to be generated by generating stations, considering the epileptic condition of the power supply and possibly planning for future increments. [25] the forecast shows that the peak load for Nigeria is between 7 pm -10 pm which then encourages people to respond by changing their consumption behavior by charging consumer that consume energy during the peak time more.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Advanced techniques like ANNs and ensemble methods, as well as statistical methods like ARIMA and Bayesian time series analysis, are effective in achieving high-accuracy predictions. In the work of [10], exponential regression was used to analyze and forecast the load needed to be generated by generating stations, considering the epileptic condition of the power supply and possibly planning for future increments. [25] the forecast shows that the peak load for Nigeria is between 7 pm -10 pm which then encourages people to respond by changing their consumption behavior by charging consumer that consume energy during the peak time more.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The range of the actual data is between 2000 and 2012, and the OLS approach showed that industrial energy consumption will reach about 1660.13 MW in 2030, 11494.83 MW for residential, 6421.09 MW for commercial and 19576.05 MW for total energy use by 2030, respectively. Similarly, Idoniboyeobu et al (2018) modelled energy demand for Nigeria by breaking down energy demand following Ezennaya et al (2014). However, the study applied exponential regression to predict energy demand, and the result showed that by 2032, residential energy demand will be 11815.66MW, 6655.06MW for commercial, 1665.48MW for industrial and 201364.41MW for total energy demand by 2032, respectively.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…The Harvey Logistic model is based on the Logistic model. From equation (10), the Harvey Logistic model is:…”
Section: Logistic Modelmentioning
confidence: 99%
“…Results showed that ANN-model performed better than the regression model for load forecasting. In [10], a study on long term electric load forecasting on the Nigerian power system using the modified form of the exponential regression model was carried out. The model was used to predict residential, commercial, and industrial load demand.…”
Section: Introductionmentioning
confidence: 99%